Improving the quality of combined EEG-TMS neural recordings: Introducing the Coil Spacer - RUDDY, KATHY; Woolley, Daniel Graham; Mantini, Dante; Balsters, Joshua; Enz, Nadja; Wenderoth, Nicole (My University, 2018)
Background: In the last decade, interest in combined transcranial magnetic stimulation (TMS) and electroencephalography (EEG) approaches has grown substantially. Aside from the obvious artifacts induced by the magnetic pulses themselves, separate and more sinister signal disturbances arise as a result of contact between the TMS coil and EEG electrodes. New method: Here we profile the characteristics of these artifacts and introduce a simple device – the coil spacer – to provide a platform allowing physical separation between the coil and electrodes during stimulation. Results: EEG data revealed high amplitude signal disturbances when the TMS coil was in direct contact with the EEG electrodes, well within the physiological range of viable EEG signals. The largest artifacts were located in the Delta and Theta frequency range, and standard data cleanup using independent components analysis (ICA) was ineffective due to the artifact’s similarity to real brain oscillations. Comparison with existing method: While the current best practice is to use a large coil holding apparatus to fixate the coil ‘hovering’ over the head with an air gap, the spacer provides a simpler solution that ensures this distance is kept constant throughout testing. Conclusions: The results strongly suggest that data collected from combined TMS-EEG studies with the coil in direct contact with the EEG cap are polluted with low frequency artifacts that are indiscernible from physiological brain signals. The coil spacer provides a cheap and simple solution to this problem and is recommended for use in future simultaneous TMS-EEG recordings.
PUBLISHED
Keywords: Transcranial magnetic stimulation; Electroencephalography; Independent components analysis; Neuroscience; Neuropsychology